Analisis Keamanan Jaringan Menggunakan Mikrotik Pada Lab Komputer STMIK Widuri - Seprianus Kenat (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2024)
This study discusses the network security analysis using MikroTik devices in the computer laboratory of STMIK Widuri. The main objective of this research is to evaluate the level of network security in the computer laboratory by implementing appropriate configurations using MikroTik devices. The methods employed include literature review on network security, analysis of network topology in the laboratory, and implementation of security solutions using MikroTik devices. Data collected include security testing results, network performance, and user satisfaction levels. The research findings indicate that the implementation of security solutions with MikroTik effectively enhances network security in the computer laboratory of STMIK Widuri. This study contributes to a practical understanding of using MikroTik in improving network security in campus environments